Development of a Skin Benign Tumor, Cancer and Melanoma from the View Point of Morpho Functional Zones - T. M., Yavisheva; S. D., Shcherbakov (International Journal For Research In Health Sciences And Nursing, 2018)
Development of a benign and malignant skin tumor in a morphofunctional zone in many respects depends on the quantity of cambial cells, which excite an electric field at their division, due to which the inactive Src-kinase, participating in a formation of the cytoskeleton and a differentiation, is expressed in cells. Decrease in cells number to 8 leads to formation of a benign tumor, and up to 6 – to malignant as this quantity of cambial cells can't express enough inactive Src-kinase, necessary for a normal cytoskeleton formation. The skin melanoma can develop without decrease in cambial cells number due to sharp redistribution between shares of inactive and the active Src-kinase, thus the cytoskeleton formation and cell differentiation fall.